Safe administration of drug desensitizations in pediatric patients. Issue 2 (30th December 2020) - Herr, Sarah; Ferdman, Ronald; Braskett, Melinda
Abstract: Purpose: Patients with certain types of allergic reactions to medication may safely receive the culprit medication through an elaborate allergy procedure called a drug desensitization. Nurses play a key role in this process which is only performed when a certain medication is absolutely indicated as optimal therapy. Nurses are instrumental in the planning stages of drug desensitizations for coordination of interdisciplinary care and anticipation of adverse effects. Thus, it is paramount that nurses performing this procedure understand the mechanism of desensitizations and have access to the resources needed to safely complete these procedures in pediatric patients. Conclusion: Excellence in nursing clinical acumen and a detailed order set are essential to patient safety during dug desensitization. With the following methodology and coordination by nursing, we have had great success at Children's Hospital Los Angeles in over one hundred drug desensitizations in pediatric patients which allowed them to received first line therapies. We have created order sets from published references and years of clinical experience. The nursing care of adult patients undergoing drug desensitization procedures is well described in the literature but few resources exist for pediatric nurses. There is paucity of published nursing resources for pediatric drug desensitizations. Repeated PubMed searches for "pediatric drug desensitizations" in 2019‐2020, revealed only one recent reference geared toward physicians. Practice Implications: With appropriate training, staffing, and coordination, drug desensitizations can be safely performed in pediatric patients with close observation by a multi‐disciplinary team. The bedside nurse has a pivotal role as coordinator and clinician for these high‐risk resource‐intensive procedures.